2015
DOI: 10.1177/0891243215602922
|View full text |Cite
|
Sign up to set email alerts
|

Altruistic Agencies and Compassionate Consumers

Abstract: What makes a multimillion-dollar, transnational intimate industry possible when most people see it as exploitative? Using the newly emergent case of commercial surrogacy in India, this article extends the literature on stratified reproduction and intimate industries by examining how surrogacy persists and thrives despite its common portrayal as the “rent-a-womb industry” and “baby factory.” Using interview data with eight infertility specialists, 20 intended parents, and 70 Indian surrogate mothers, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Relationships between LGBTQ + parents and people who help them to reproduce also complicate the distinctions made in anthropological theories of 'gift relationships' based on reciprocity, as opposed to 'commodity relationships' based on commercial exchange: recent research shows that potential or actual use of reproductive technologies, including surrogacy, is often approached simultaneously both as a gift and a commodity relationship between users and providers (Berend, 2016;Dow, 2016;Jacobson, 2016;Mohr, 2015;Ragone, 1994;Smietana, 2017;Thompson, 2014). However, in some contexts such as commercial surrogacy in India, the fertility industry was found to prevent kinship between surrogate mothers, egg donors/providers and intended parents, even though surrogate mothers often attempted to approach surrogacy as both commodity and gift, and a potential for building some kind of queer kinship was expressed by some participants in commercial surrogacy transactions (Nadimpally et al, 2016;Majumdar, 2017;Pande, 2011;Rudrappa, 2015;Rudrappa and Collins, 2015) Reproductive justice Reproductive justice expands the narrow focus on contraceptive and abortion access and fertility services of white middle-class reproductive rights movements, and incorporates families' rights to be able to raise their children free from economic and state violence (Price, 2010). The shift from reproductive rights to reproductive justice includes pivoting away from the idea of increasing reproductive choice and toward increased reproductive access and human rights.…”
Section: Queer Kinshipmentioning
confidence: 99%
“…Relationships between LGBTQ + parents and people who help them to reproduce also complicate the distinctions made in anthropological theories of 'gift relationships' based on reciprocity, as opposed to 'commodity relationships' based on commercial exchange: recent research shows that potential or actual use of reproductive technologies, including surrogacy, is often approached simultaneously both as a gift and a commodity relationship between users and providers (Berend, 2016;Dow, 2016;Jacobson, 2016;Mohr, 2015;Ragone, 1994;Smietana, 2017;Thompson, 2014). However, in some contexts such as commercial surrogacy in India, the fertility industry was found to prevent kinship between surrogate mothers, egg donors/providers and intended parents, even though surrogate mothers often attempted to approach surrogacy as both commodity and gift, and a potential for building some kind of queer kinship was expressed by some participants in commercial surrogacy transactions (Nadimpally et al, 2016;Majumdar, 2017;Pande, 2011;Rudrappa, 2015;Rudrappa and Collins, 2015) Reproductive justice Reproductive justice expands the narrow focus on contraceptive and abortion access and fertility services of white middle-class reproductive rights movements, and incorporates families' rights to be able to raise their children free from economic and state violence (Price, 2010). The shift from reproductive rights to reproductive justice includes pivoting away from the idea of increasing reproductive choice and toward increased reproductive access and human rights.…”
Section: Queer Kinshipmentioning
confidence: 99%
“…Schurr and Militz (2018) argue commodification always takes place, regardless of how it is framed, because surrogacy delineates the intimate boundaries of families through the processes of attachment and detachment. Thus, to justify the aspect of choice in their participation, market actors may utilize moral frames of compassion and altruism, emphasizing how surrogacy can empower disadvantaged women to further their reproductive rights (Rudrappa & Collins, 2015). Khader (2013) suggests gender, race, and class oppression, which is often imagined to subject women to more harm, can instead "mitigate the negative welfare effects of being a commercial surrogate" (p.69), claiming they are less likely to be taken advantage of and are more likely to acquire significant financial benefits when compared to their Western counterparts.…”
Section: Discourses On Surrogacymentioning
confidence: 99%
“…A small but growing number of research studies suggest that surrogacy has become a particularly popular pathway to parenthood for cisgender gay men (Patterson & Tornello, 2010) and that most of the gay men who access surrogacy are White and wealthy (see chapter "Gay Men and Surrogacy"). Surrogacy has produced a new layer of racialized, gendered, classed, and colonial stratification on a global level (DasGupta & DasGupta, 2010;Gondouin, 2012;Nebeling Petersen, 2018;Pande, 2015;Rudrappa & Collins, 2015;Vora, 2012). While many gay men work with altruistic surrogates (i.e., surrogates who do not receive monetary compensation), commercial surrogacy is fast becoming a common feminized vocation (Jacobson, 2016).…”
Section: Transracial Adoption and Surrogacymentioning
confidence: 99%
“…In their interviews with gay men from the USA and Australia who had availed commercial surrogacy services in India, Rudrappa and Collins (2015) found that men used "strategic moral frames" of surrogates' financial empowerment, access to reproductive rights, and liberation from patriarchy as justification for surrogacy. But the authors' interviews with the surrogates reveal how these moral frames were systematically created by the multimillion-dollar surrogacy industry by maintaining a commercial distance between the surrogate mothers and their Western clients.…”
Section: Transracial Adoption and Surrogacymentioning
confidence: 99%